PERAN ADVERSITY QUOTIENT TERHADAP FEAR OF FAILURE PADA MAHASISWA BIDIKMISI TINGKAT AKHIR (The Role of Adversity Quotient Toward Fear of Failure On Final Year Bidikmisi Students - Ayu Purnamasari Ayu; Novia Ananda Putri (Universitas Bunda Mulia, 2022)
ABSTRACT Bidikmisi student is someone who gets educational financial assistance in the form of tuition fees with a predetermined time limit, and required to graduate on time. The maximum funding limit for undergraduate students is eight semesters. The existence of these demands makes Bidikmisi final year students feel burdened, and assume that if they cannot achieve the target they must bear the cost of their own education. In addition, these demands cause Bidikmisi students to experience a fear of failure. The demands and problems in the midst of economic limitations require Bidikmisi students to get out of the situation with an adversity quotient. This research was conducted with the aim of knowing the role of adversity quotient on fear of failure in final year Bidikmisi students. This research uses quantitative methods. The participants used in this study were 145 people, and the trial was conducted on 30 people. Research participants were selected using purposive sampling. There are two measuring tools used, namely the fear of failure scale and the adversity quotient scale. The results of data analysis were carried out using a simple regression method. The results of the regression analysis showed that the adversity quotient had a significant role in the fear of failure with a value of R = 0.514, R-square = 0.264, F = 51.277, and p = 0.000 (p < 0.05). Thus, the results of this study prove that the hypothesis proposed by the researcher is accepted, the adversity quotient contributes to the fear of failure.Keywords: Fear of failure, adversity quotientABSTRAKMahasiswa bidikmisi adalah mahasiswa yang mendapatkan bantuan dana pendidikan berupa tanggungan biaya perkuliahan sampai dengan batas waktu yang telah ditetapkan, dan dituntut untuk dapat lulus tepat waktu. Maksimal batas pembiayaan bagi mahasiswa S1 adalah delapan semester. Adanya tuntutan tersebut membuat mahasiswa bidikmisi tingkat akhir merasa terbebani, dan beranggapan jika tidak dapat mencapai target tersebut diharuskan menanggung biaya pendidikan sendiri. Selain itu, tuntutan tersebut mengakibatkan mahasiswa bidikmisi mengalami fear of failure. Tuntutan dan permasalahan ditengah keterbatasan ekonomi mengharuskan mahasiswa bidikmisi untuk keluar dari situasi tersebut dengan adversity quotient. Penelitian ini dilakukan dengan tujuan untuk mengetahui peran adversity quotient terhadap fear of failure pada mahasiswa bidikmisi tingkat akhir. Penelitian ini merupakan penelitian kuantitatif. Jumlah partisipan penelitian sebanyak 145 orang, dan uji coba dilakukan terhadap 30 orang. Partisipan penelitian dipilih dengan menggunakan purposive sampling. Alat ukur yang digunakan ada dua yakni skala fear of failure, dan skala adversity quotient. Hasil analisis data dilakukan dengan menggunakan metode regresi sederhana. Hasil analisis regresi menunjukkan bahwa adversity quotient memiliki peran yang signifikan terhadap fear of failure dengan nilai R = 0,514, R-square = 0,264, F = 51,277, dan p = 0,000 (p < 0,05). Dengan demikian, hasil penelitian ini membuktikan hipotesis yang diajukan peneliti diterima, adanya kontribusi adversity quotient terhadap fear of failure.Kata Kunci: Fear of failure, adversity quotient